High Glass‐Transition Temperature Polymer Networks Harnessing the Dynamic Ring Opening of Pinacol Boronates. Issue 35 (25th July 2019) - Brunet, Juliette; Collas, Franck; Humbert, Matthieu; Perrin, Lionel; Brunel, Fabrice; Lacôte, Emmanuel; Montarnal, Damien; Raynaud, Jean
Abstract: Differential scanning calorimetry of high molar mass poly(4‐vinylphenylboronic acid, pinacol ester)s evidenced unusual reactive events above 120 °C, resulting in a high glass‐transition temperature of 220 °C. A reversible ring‐opening reactivity of pinacol boronates is proposed, involving a nucleophilic attack on the sp 2 boron and subsequent bridging between boron atoms by interconnected pinacol moieties to form a densely crosslinked network with high Tg . FTIR, solid‐state NMR investigations, and rheology studies on the polymer as well as double‐tagging analyses on molecular model structures and theoretical calculations further support this hypothesis and indicate a ring‐opening inducing crosslinking. When diluted in an apolar solvent such as toluene, the polymer network can be resolubilized via ring closing, thus recovering the entropically favored linear chains featuring cyclic boronate esters. Abstract : Styrenic‐based polymers bearing pendent pinacol boronate ester groups are able to crosslink into dense networks with glass transition temperatures as high as 220 °C. This crosslinking is based on an overlooked dynamic ring opening of cyclic boronates promoting bridging between boron atoms, and it is fully reversible upon dilution at ambient temperatures.